OPTIMALISASI POTENSI DESA DONOMULYO MELALUI DESAIN LAYOUT PERKEBUNAN TEBU DAN MEDIA DIGITAL - Muhammad Aris Ichwanto; Mohammad Musthofa Al Ansyorie; Imam Alfianto; Surya Adi Saputra; Nur Ira Mega Maharani; Eviola Sukma Putri; Fariski Ismail Hasan (Sekolah Vokasi Universitas Diponegoro, 2021)
Donomulyo is one of the villages in Malang district with several potential villages, including plantations, tourism, and religion. Sugarcane plantations are the village's leading commodity with strategic value based on physical considerations regarding soil conditions, water conditions, climate, socio-economics, and the profession of the majority of villagers. The area of the sugar cane plantation reaches around 51 hectares. However, these potentials are not well known by the public. This layout design is used as an illustration of the development of sugarcane plantations in Donomulyo Village. The development of this potential will lead to the creation of educational tourism for cultivation and compost sugarcane. Therefore, making this layout design is an attempt to optimize the village's potency, especially sugarcane plantations, as an introduction to educational facilities for the community and public. The cultivation and compost educational tourism will become a center of the agricultural sector in Donomulyo Village and will certainly provide additional knowledge to the community regarding the cultivation and maintenance of the agricultural and plantation sectors, which are the professions of the majority of villagers. The existence of this educational tourism will also be a way to improve the economy of Donomulyo Village.